Effects of Different Chair-Based Exercises on Salivary Biomarkers and Functional Autonomy in Institutionalized Older Women. Issue 1 (2nd January 2019) - Rieping, Taís; Furtado, Guilherme Eustáquio; Letieri, Rubens Vinícius; Chupel, Matheus Uba; Colado, Juan C.; Hogervorst, Eef; Filaire, Edith; Teixeira, Ana Maria Miranda Botelho; Ferreira, José Pedro
ABSTRACT: Purpose : The aim of this study was to test the effects of chair-based exercise programs on salivary stress hormones, physical fitness, and functional autonomy of institutionalized older women.Method : In total, 47 participants (80 ± 8.04 years old) were recruited and allocated into three groups: chair-based aerobic exercises (CAE, n = 19), chair-based elastic-band strength exercises (CSE, n = 15), and a control group (CG, n = 13). A 14-week exercise intervention was done for the CAE and CSE groups, two times per week, in no consecutive days. Members of the CG did not participate in any type of exercise but kept their regular lifestyle. Fear of falling, autonomy, physical fitness, salivary cortisol, and alpha-amylase levels were assessed before and after the intervention.Results : The CAE group improved upper and lower body strength, agility–dynamic balance, and autonomy, with fear of falling decreasing significantly ( p < .05, moderate effect size). Both exercise groups showed a trend toward an increase in salivary alpha-amylase levels (CAE = 43%, d = .31, and CSE = 44%, d = .41).Conclusion : Both exercise programs were able to improve functional autonomy, even in elders older than 80 years of age. It might be interesting to investigate the effectiveness of combining both aerobic and strength exercises in a unique protocol. The modulation effect of exercise in the hormonal responses needs to be further explored.